Electoral Bottlenecks and Problems of Governance in Nepal - Bharadwaj, Narad; Dungana, Shiva K.; Upreti, Bishnu Raj (Kasarinlan: Philippine Journal of Third World Studies; Vol 19 No 2 (2004): Electoral Politics 1, 2007)
This paper assesses the electoral system and problems of governance in Nepal focusing on various phases of political developments since the 1950s. It analyzes the setbacks encountered in the democratization of the country. The article explains the function of Nepal’s electoral system at various junctures of its recent history and traces the struggle of the people for democratic governance against an entrenched feudal culture of authoritarianism. It analyzes the role of the king, the political parties, and the geopolitics in the region in obstructing democratization, good governance and accountability. Finally, it shows how electoral deviations and lack of good governance have combined to engender Maoist insurgency. The paper argues that only a peaceful solution of the present day conflict brought about by Maoist insurgency will strengthen the democracy in Nepal.
Keywords: Constitution of Nepal; electoral system; governance; Maoist insurgency; multiparty democracy; panchayat system